2018
DOI: 10.1080/14670100.2017.1416759
|View full text |Cite
|
Sign up to set email alerts
|

Comparing eSRT and eCAP measurements in pediatric MED-EL cochlear implant users

Abstract: eSRTs were significantly higher than eCAP thresholds and eSRT and eCAP profiles were generally different from each other reducing the clinical relevance of eCAP testing for setting MCLs across the array. Additionally, the eSRT measurements were faster to record than the eCAP threshold and slope determination measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 39 publications
0
15
0
4
Order By: Relevance
“…The eSRT levels were not found statistically higher than the eCAP thresholds in the current study. Kosaner et al (2018) and Walkowiak et al (2011) reported contrary results.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…The eSRT levels were not found statistically higher than the eCAP thresholds in the current study. Kosaner et al (2018) and Walkowiak et al (2011) reported contrary results.…”
Section: Discussionmentioning
confidence: 90%
“…Kosaner et al evaluated the eSRT values and eCAP thresholds in children with Med-El CI and found out that eCAP thresholds are significantly lower than the eSRT levels (Kosaner et al, 2018). Walkowiak et al (2011) evaluated the eSRT levels and eCAP thresholds in 16 adults and 14 children with Med-El Pulsar CI100.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Este último ha sido de utilidad para confirmar la funcionalidad del implante en el tiempo y para estimar el umbral de confort 12 . Sin embargo, los resultados obtenidos con el ECAP no se correlacionan necesariamente con las mediciones del eREE, y requiere de más tiempo para realizar el examen 13 . En pacientes implantados que presentan comorbilidades, existe una cooperación limitada lo que hace que la obtención de los valores del umbral de confort no pueda registrarse en forma adecuada.…”
Section: Discussionunclassified